Greenpeace Advocacy Campaign on Forest Fire Prevention and Peat Preservation as Climate Crisis Solution - Sari, Inrinofita; Syukri, Ahmad (Jurnal Noken: Ilmu-Ilmu Sosial, 2025)
This study aims to analyze Greenpeace's advocacy campaign on forest fire prevention and peatland conservation as a solution to overcome the climate crisis. Greenpeace, as an international environmental organization, has been running advocacy campaigns to reduce land damage and support peatland conservation. This study employs a qualitative research method with qualitative data analysis (QDA) and adopts a descriptive approach. Data was obtained from online media sources, websites, and previous studies related to Greenpeace campaigns. Data processing was carried out using NVivo 12 Plus software, utilizing the Crosstab Query feature to visualize the relationship between variables and a Word Cloud to identify the dominant words in the data. The results of the analysis indicate that Greenpeace's advocacy campaigns play a significant role in driving change, both by raising public awareness about the importance of preserving peat ecosystems and by advocating for more sustainable forest management. Through these campaigns, the understanding of the need for more environmentally friendly management will continue to grow. The novelty of this research lies in the use of Nvivo-based digital analysis to map the interrelationships between campaign elements, including advocacy messages, communication approaches, and public responses, thereby producing a more systematic understanding of the effectiveness of Greenpeace's campaign strategies on the issues of forest fire prevention and peatland conservation